1993
DOI: 10.1210/en.132.5.1913
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of thyroid hormone receptors and c-erbA expression during brown adipose tissue development: evidence of fetal acquisition of the mature thyroid status

Abstract: We have determined the developmental changes in thyroid hormone receptor expression and thyroid hormone status in rat brown adipose tissue (BAT). The present study demonstrates that c-erbA alpha and -beta genes are expressed in the developing BAT. The 6.5-kilobase (kb) beta 1, 2.6-kb alpha 2, 5.5-kb alpha 1, and 6.6-kb alpha transcripts showed peak values on day 20 of fetal life. High affinity T3-binding sites were found in fetal BAT. Binding capacity was similar (18-day-old fetuses) or higher (20-day-old fetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Regulation of fat mass is controlled by multiple neuroendocrine signals. Thyroid hormones are predominantly considered as hormones involved in adipose tissue development and metabolism (Levacher et al, 1984;Tuca et al, 1993). Their most obvious and well-known action is an increase in basal energy expenditure obtained acting on adipose tissue metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of fat mass is controlled by multiple neuroendocrine signals. Thyroid hormones are predominantly considered as hormones involved in adipose tissue development and metabolism (Levacher et al, 1984;Tuca et al, 1993). Their most obvious and well-known action is an increase in basal energy expenditure obtained acting on adipose tissue metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR activity may be released from suppression by TR due to decreased number of TR during fasting, resulting in the increased transcriptional levels of enzymes regulating fatty acid ␤-oxidation such as aox gene. Furthermore, TR expression is regulated by hormones (54) and strictly controlled during ontogeny and development (55)(56)(57)(58). TRs exert their effects on lipid metabolism through convergence of PPAR signaling pathways.…”
Section: Table I Protein Expression Of Tra1 and Its Dbd Mutant In Cosmentioning
confidence: 99%
“…In rat, northern blot analysis showed that TRa mRNA concentration increased in brain, liver, and brown adipose tissue from 18 days of development onwards to reach its highest level perinatally (Strait et al 1990, Tuca et al 1993. TRb mRNA also increased perinatally in brain, but was reported to reach its peak only in the second postnatal week (Strait et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…TRb mRNA also increased perinatally in brain, but was reported to reach its peak only in the second postnatal week (Strait et al 1990). In contrast, TRb mRNA decreased perinatally in liver and brown adipose tissue (Strait et al 1990, Tuca et al 1993. In the developing nervous system of the rat, the highest cellular concentration of TRa mRNAs was found in the areas of neuronal differentiation such as the fetal neocortical plate, whereas TRb mRNAs were largely restricted to the zones with neuroblast proliferation, such as the germinal trigone and the cortical ventricular layer (Bradley et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation